A forced convection of water-aluminum oxide nanofluids in a square cavity containing a circular rotating disk of unit speed with high Reynolds number: A Comsol Multiphysics study. (November 2022) - Usman,; Memon, Abid Ali; Anwaar, Haris; Muhammad, Taseer; Alharbi, Ahmad Ayyad; Alshomrani, Ali Saleh; Aladwani, Yaser Rajeh
Abstract: This research article concentrates on forced convection with a high Reynolds number of the water-alumina-based nanofluid in the square cavity containing a rotating disk with a unit speed. A very dense mesh is used to obtain the numerical results with the finite element package of COMSOL Multiphysics 5.6. For the research study, we select the parameters, the Reynolds number (10 6 to 1.005 × 10 6 ), a radius of the rotating disk (0.1m–0.2 m), and volume fraction (0.001–0.009 and 0.01–0.05). About 54 simulations are obtained using the Rayleigh numbers 7 × 10 6 to 1.54 × 10 6 and keeping the Prandtl number less than 0.7. The outcomes will be validated with correlations from the local Nusselt number literature and the independent mesh study. The results will be displayed with the surface plots and graphs for temperature, average temperature, local and average Nusselt number, mass flow rate, skin friction coefficient, and average values on the surface of the circular rotating disk. A correlation originated between the temperature as an average on the surface of a rotating cylinder and mass flow rate, which describe a negative association between the mass flow rate and the average temperature on the surface of a circular disk. It was concluded that the coefficient of skin friction improves with an upsurge in volume fraction of the nanofluid, whereas it shows a non-functionality with an average Nusselt number when an increment is made in the radius of a circular disk.